2015
DOI: 10.1111/bjd.13385
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hidradenitis suppurativa with intralesional photodynamic therapy using a laser diode attached to an optical cable: a promising new approach

Abstract: DEAR EDITOR, Hidradenitis suppurativa (HS) or acne inversa is a chronic inflammatory process that affects the apocrine glands of the skin folds. Recent histological investigations suggest that HS involves the entire hair follicle with follicular hyperkeratosis in early stages. HS has a prevalence of approximately between 1% and 2% of the general population and most often affects © 2014 British Association of Dermatologists British Journal of Dermatology (2015)Funding sources: none.Conflicts of interest: none d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 10 publications
0
30
0
9
Order By: Relevance
“…There appears to be RCT evidence behind using follicular laser ablation for early stage disease . Response to photodynamic therapy is variable; larger and randomized controlled trials are needed. External beam radiation therapy has an unclear role in the treatment of HS, as there are currently only case reports in the literature …”
Section: Scientific Session 6: Surgical and Laser Management Of Hidramentioning
confidence: 99%
“…There appears to be RCT evidence behind using follicular laser ablation for early stage disease . Response to photodynamic therapy is variable; larger and randomized controlled trials are needed. External beam radiation therapy has an unclear role in the treatment of HS, as there are currently only case reports in the literature …”
Section: Scientific Session 6: Surgical and Laser Management Of Hidramentioning
confidence: 99%
“…In these cases, treatments were more tolerable for subjects treated with blue light than with intense pulsed light. Uncertain results have been obtained with intralesional PDT [74][75] . Agut-Busquet et al [76] recently reported a retrospective experience in the treatment of HS with PDT using intralesional methylene blue and a 635-nm light-emitting diode lamp in 7 patients.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Recently, RodriguezPrieto et al used intralesional PDT for the treatment of HS and showed good e®ect. 16,17 Intralesional PDT will be a good choice for late sinus/¯stula lesions. Saraceno et al reported a case of HS achieved 80% remission of skin lesions treated by nine times of Methyl aminolaevulinate PDT.…”
Section: Discussionmentioning
confidence: 99%